Relationships Between Perceived Importance of Chaplain Presence and Health Professionals’ Emotional Well-Being in the United States - Gaines, Adam F.; Rangel, Teresa L.; Freedberg, Rachel; Doucette, Sheila; Stengem, Danell; Timmerman, Rosemary; Roney, Jamie; Arenivar, Patrick; Patterson, Angela; Long, JoAnn; Sumner, Sarah; Bock, Dawn; et al. (2023)
Hospital-based chaplains receive specialized training to provide spiritual support to patients and healthcare staff during difficult health transitions. However, the impact of perceived chaplain importance on healthcare staff’s emotional and professional well-being is unclear. Healthcare staff (n = 1471) caring for patients in an acute care setting within a large health system answered demographic and emotional health questions in Research Electronic Data Capture (REDCap). Findings suggest that as perceived levels of chaplain importance increase, burnout may decrease and compassion satisfaction may improve. Chaplain presence in the hospital setting may support healthcare staff emotional and professional well-being following occupational stressors including COVID-19-related surges.
Keywords: Burnout; Chaplains; compassion satisfaction; Emotional Health; Healthcare staff; Stress